2003
DOI: 10.5688/aj670389
|View full text |Cite
|
Sign up to set email alerts
|

Excellence in Curriculum Development and Assessment

Abstract: Pharmacy and other health sciences educators have often faced curriculum and assessment issues. However, as expectations for accountability and assessment have continued to grow for higher education institutions, there is increasing concern about the development of assessment plans and the appropriate use of assessment data. A variety of approaches have been used for development of both curriculum and program assessment plans. Although there is no single correct method for accomplishing either task, there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 31 publications
0
75
0
1
Order By: Relevance
“…Students were expected to engage in all pharmaceutical care activities using the framework defined by Strand and Hepler. 13,14 Prior to the start of the APPE, all students were required to purchase and review the APPE manual, attend a mandatory face-to-face orientation session, and complete an open manual, online quiz reinforcing the APPE expectations and requirements (this included a discussion on the type and extent of the documentation required). Preceptors were also provided with a copy of the APPE manual; however, no face-to-face education was offered.…”
Section: Interventionmentioning
confidence: 99%
“…Students were expected to engage in all pharmaceutical care activities using the framework defined by Strand and Hepler. 13,14 Prior to the start of the APPE, all students were required to purchase and review the APPE manual, attend a mandatory face-to-face orientation session, and complete an open manual, online quiz reinforcing the APPE expectations and requirements (this included a discussion on the type and extent of the documentation required). Preceptors were also provided with a copy of the APPE manual; however, no face-to-face education was offered.…”
Section: Interventionmentioning
confidence: 99%
“…The paper by Abate, Stamatakis, and Haggett provided an analysis of contemporary issues in higher education and health professions education related to curriculum development, instructional design and delivery, student assessment, and program assessment, and factors necessary to assure quality instructional programs in pharmaceutical education. 15 • Ongoing: AACP conducts institutional research and provides institution-specific data and comparisons for assessment and benchmarking purposes.…”
Section: Recommendationmentioning
confidence: 99%
“…After a review of the literature in 2000, Abate and colleagues found that most colleges and schools of pharmacy were "…in only the early stages of establishing an institutional culture of assessment and comprehensive outcomes assessment plans…" 15 The Assessment Culture Matrix from the Higher Learning Commission provides a framework and markers used to determine the extent to which a program, college/school, or university has evolved a culture of assessment. In each of four clusters (institutional culture, shared responsibility, institutional support, and efficacy of assessment), descriptions of characteristics are provided at three levels of implementation (beginning implementation of assessment programs, making progress in implementing assessment programs, and maturing stages of continuous improvement) to assist programs in understanding and gauging the strength of their assessment programs.…”
Section: Assessment Resourcesmentioning
confidence: 99%
“…5 There also are published comprehensive reviews that outline the rationale and basic principles for assessment in pharmacy education. 6,7 However, no method for comparing the planned pharmacy curriculum to the delivered instruction was found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…We define curriculum to include content, student learning outcomes, instructional methods and approaches, teaching and learning processes, and student, instructor, and program assessment. 6,8 Ongoing program assessment also should assist faculty members in making informed changes in course structures and instructional methods. Information collected should provide evidence of successes as well as suggest specific steps, resources, and support needed for improvements.…”
Section: Introductionmentioning
confidence: 99%